2020
DOI: 10.1007/s10637-020-00927-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled study of B-cell lymphoma 2 homology 3 mimetic gossypol combined with docetaxel and cisplatin for advanced non-small cell lung cancer with high expression of apurinic/apyrimidinic endonuclease 1

Abstract: Summary Background Overexpression of apurinic/apyrimidinic endonuclease 1 (APE1) is an important cause of poor chemotherapeutic efficacy in advanced non-small cell lung cancer (NSCLC) patients. Gossypol, a new inhibitor of APE1, in combination with docetaxel and cisplatin is believed to improve the efficacy of chemotherapy for advanced NSCLC with high APE1 expression. Methods Sixty-two patients were randomly assigned to two groups. Thirty-one patients in the experimental group received 75 mg/m2 docetaxel and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…A study consisting of sixty-two advanced NSCLC patients with no previous history of platinum-based chemotherapy showed that patients treated with gossypol along with the assigned docetaxel and cisplatin treatment experienced greater PFS and OS than those in the control group receiving placebo along with the same docetaxel and cisplatin regimen. Though there were no significant differences in PFS, OS, and adverse events between treatment and control groups, the addition of gossypol was well tolerated, and the results encourage larger studies to investigate the drug’s therapeutic potential [ 133 ].…”
Section: Current Treatment Strategies and Future Perspectivesmentioning
confidence: 99%
“…A study consisting of sixty-two advanced NSCLC patients with no previous history of platinum-based chemotherapy showed that patients treated with gossypol along with the assigned docetaxel and cisplatin treatment experienced greater PFS and OS than those in the control group receiving placebo along with the same docetaxel and cisplatin regimen. Though there were no significant differences in PFS, OS, and adverse events between treatment and control groups, the addition of gossypol was well tolerated, and the results encourage larger studies to investigate the drug’s therapeutic potential [ 133 ].…”
Section: Current Treatment Strategies and Future Perspectivesmentioning
confidence: 99%
“…In three trials, AT-101 was tested combined with one standard chemotherapeutic (1× topotecan, 2× docetaxel) [97,101,102]. Double standard treatment in combination with AT-101 was investigated in four studies [88,96,99,100]. Notably, one cisplatin and radiation regimen was established [57].…”
Section: Trials Determining Therapeutic Effect and Toxicity Of Single...mentioning
confidence: 99%
“…In addition to small cell lung cancer, there are two further double-blind, placebocontrolled, randomized phase II studies evaluating pharmacological activity of gossypol/AT-101 in non-small cell lung cancer [96,101]. Ready at al.…”
Section: Trials Determining Therapeutic Effect and Toxicity Of Single...mentioning
confidence: 99%
“…Animal studies [91] APX2014 [91] Gossypol [106] Inhibitor III 3 [107] Endonuclease inhibitor (Compound #3) [108] (Continued)…”
Section: Apx2009mentioning
confidence: 99%
“… 91 Gossypol in combination with docetaxel and cisplatin improved the efficacy of chemotherapy for advanced non-small-cell lung cancer (NSCLC). 106 Inhibitor III showed substantial antileukemic efficacy, 107 and compound #3 affected mitochondrial activity and suppressed colorectal cancer. 108 RN7-60 and RN10-52 had a greater effect than APX3330 on ovarian cancer cells, and RN8-51 had an effect similar to that of APX3330.…”
Section: The Abca1-ape1/ref-1 Axis As a Drug Targetmentioning
confidence: 99%